2020
DOI: 10.1016/j.jsxm.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Practice of Sexual Medicine in the Time of COVID-19 in the United Kingdom

Abstract: Background: On 23rd March 2020, the UK government released self-isolation/social distancing guidance to reduce the risk of transmission of SARS-CoV-2. The influence such guidance has on sexual activity is not known. Aim: To investigate levels and correlates of sexual activity during COVID-19 self-isolation/social distancing in a sample of the UK public. Methods: This paper presents preplanned interim analyses of data from a cross-sectional epidemiological study, administered through an online survey. Outcomes:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
172
1
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(213 citation statements)
references
References 14 publications
16
172
1
15
Order By: Relevance
“…In a study with 868 participants which was conducted in Britain during the COVID-19 pandemic, being sexually active, which was defined as having at least one sexual intercourse per week, was related to being a young male, being married or in a domestic partnership, consuming alcohol and practicing self-isolation/social distancing for a high number of days. 10 Similarly, alcohol consumption, marital status, having a regular sexual partner, and being a woman was associated with worsening sexual functions according to our study results during the COVID-19 pandemic. Interestingly, in our study population, the mean number of sexual intercourse tended to decrease while the mean number of masturbation had increased values when compared to pre-pandemic period.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In a study with 868 participants which was conducted in Britain during the COVID-19 pandemic, being sexually active, which was defined as having at least one sexual intercourse per week, was related to being a young male, being married or in a domestic partnership, consuming alcohol and practicing self-isolation/social distancing for a high number of days. 10 Similarly, alcohol consumption, marital status, having a regular sexual partner, and being a woman was associated with worsening sexual functions according to our study results during the COVID-19 pandemic. Interestingly, in our study population, the mean number of sexual intercourse tended to decrease while the mean number of masturbation had increased values when compared to pre-pandemic period.…”
Section: Discussionsupporting
confidence: 76%
“…8,9 Despite this knowledge, very few articles have investigated the effects of the COVID-19 pandemic on sexual life. [10][11][12] Reducing in the sexual activity and related factors were determined in a recent study which was conducted in the British public during the COVID-19 pandemic. 10 Moreover, newly detailed reports were presented about the challenges in the practice of sexual medicine from several countries as sexual health is being an important healthcare issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies on sexuality during the lockdown considered the frequency of sexual activity or sexual intercourses. In the United Kingdom and Spain, respectively, only 41 and 39% of the participants had maintained the same frequency ( Ibarra et al, 2020 ); decrease in sexual intercourse frequency was found in 60% of United Kingdom participants ( Jacob et al, 2020 ), and a decrease in sexual activity was found in 37% of the Chinese participants ( Li G. et al, 2020 ). In three south-east Asian countries, nearly 70% of the participants engaged in sexual activity with their partner one to five times a week or more, with a considerable increase from before the lockdown ( Arafat et al, 2020 ); similar results were found in Turkish women ( Yuksel and Ozgor, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, partners have lost their privacy due to the constant presence of children or other family members, whereas on the other hand, forced lockdown can exacerbate existing relationship problems. Fear of being infected also drastically reduced physical contact in couples: a decrease in vaginal sex was found in United States couples ( Hensel et al, 2020 ), while in the United Kingdom, 60.1% of the participants did not engage in sexual activity during the self-isolation period, while the remaining 39.9% had sex at least once a week, where being male, young, and married was associated with an increase in sexual activity, and a prolonged period of quarantine was associated with an increase in sexual activity, probably due to reduced stress and anxiety or as a diversion to deal with boring days ( Jacob et al, 2020 ). In another study, 43.5% of the participants from several countries reported a decline in sexual quality along with a severe reduction in the frequency of intercourse during lockdown compared to the previous year, even if many people living with the partner have experimented new sexual positions, BDSM, and acted out some sexual fantasies, while those who did not live with the partner tried new activities such as sexting ( Lehmiller et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%